Clinical and Economic Evaluation of Acupuncture for Opioid-Dependent Patients Receiving Methadone Maintenance Treatment: The Integrative Clinical Trial and Evidence-Based Data - Wen, Hao; Wei, Xiaojing; Ge, Shuqi; Zeng, Jingchun; Luo, Wen; Chen, Rouhao; Dong, Yu; Xiao, Songhua; Lai, Yunfeng; Lu, Liming (Frontiers in Public Health, 2021)
Objective: From the health care and societal perspectives, this study aimed to evaluate the clinical and economic effects of acupuncture as an adjunctive therapy for patients receiving methadone maintenance treatment (MMT). Methods: We conducted a parallel-arm RCT in China in 2019. Patients were included who meet the diagnostic criteria and receive MMT for more than 30 days. Patients were 1:1 randomization to the exposed group (acupuncture plus MMT) or control group (MMT). Daily methadone dosage, drug cravings using the VAS score, and insomnia using the Pittsburgh Sleep Quality Index (PSQI) were chosen as the effectiveness indexes and the quality-adjusted life years (QALYs) as utility index. Results: 123 patients were included. The exposed group was significant (P<0.05) better than a control group in the improvement of daily methadone dosage (17.68 VS 1.07), VAS (38.27 VS 2.64), and PSQI (2.18 VS 0.30). The QALY was 0.0784 (95%CI: 0.0761 to 0.0808) for exposed group and 0.0762 (95%CI: 0.0738 to 0.0787) for control group. Total cost of exposed group (2869.50 CNY) was higher than control group (2186.04 CNY). ICER of daily methadone dosage (41.15), VAS (17.86), and PSQI (313.51) showed not economically efficient. ICUR (310,663.64 CNY/QYLY) was higher than the cost suggested by WHO. Conclusion: Acupunctur as adjuvant therapy for MMT patients, realizes its cost-effectiveness by reducing the dosage of methadone, improving drug cravings, and alleviating insomnia. It has the cost-utility of improving the quality of life, but since it exceeds the cost of the society's willingness to pay, further study is needed.